Simulation training to improve 9-1-1 dispatcher identification of cardiac arrest: A randomized controlled trial. (October 2017) - Meischke, Hendrika; Painter, Ian S.; Stangenes, Scott R.; Weaver, Marcia R.; Fahrenbruch, Carol E.; Rea, Tom; Turner, Anne M.
Abstract: Background: The objective of this study was to test the effectiveness of simulation training, using actors to make mock calls, on improving Emergency Medical Dispatchers' (EMDs) ability to recognize the need for, and reduce the time to, telephone-assisted CPR (T-CPR) in simulated and real cardiac arrest 9-1-1 calls. Methods: We conducted a parallel prospective randomized controlled trial with n = 157 EMDs from thirteen 9-1-1 call centers. Study participants were randomized within each center to intervention (i.e., completing 4 simulation training sessions over 12-months) or control (status quo). After the intervention period, performance on 9 call processing skills and 2 time-intervals were measured in 2 simulation assessment calls for both arms. Six of the 13 call centers provided recordings of real cardiac arrest calls taken by study participants during the study period. Results: Of the N = 128 EMDs who completed the simulation assessment, intervention participants (n = 66) performed significantly better on 6 of 9 call processing skills and started T-CPR 23 s faster (73 vs 91 s respectively, p < 0.001) compared to participants in the control arm (n = 62). In real cardiac arrest calls, EMDs who completed 3 or 4 training sessions were more likely to recognize the need for T-CPR for more challenging cardiac arrest calls than EMDs who completed fewer than 3, including controls who completed no training (68% vs 53%, p = 0.018). Conclusions: Simulation training improves call processing skills and reduces time to T-CPR in simulated call scenarios, and may improve the recognition of the need for T-CPR in more challenging real-life cardiac arrest calls. Clinical trial registration: http://www.clinicaltrials.gov Trial # NCT01972087.